A Novel Method to Quantify Self-Healing Capabilities of Fiber-Reinforced Polymers - Scazzoli, Cecilia; Trigueira, Robin; Cohades, Amaël; Michaud, Véronique (Frontiers in Materials, 2022)
Research on self-healing fibre reinforced polymers (FRPs) has been going on since the early 2000, with the exploration of several routes such as the incorporation of capsules or hollow channels containing a healing agent and the use of intrinsically healable matrices. Apart from the challenge to maintain high volume fraction of reinforcing fibers and to maintain adequate mechanical properties for the healable composite, another practical challenge has been to propose adequate characterization methods which enable to quantitatively assess the healing efficiency of the matrix material in the composite, and to compare the different materials solutions. Many different testing methods exist, but these are often either not fully representative of real damage occurring throughout the lifetime of a composite part, cumbersome or require the use of large amounts of material. In addition, in some tests, fiber breakage takes place and avoids a direct comparison between matrix healing properties within the composite and in bulk form. The present work aims at presenting a novel and practical alternative to evaluate the healing efficiency of self-healing FRPs. The capacity to recover low-velocity impact damage has been evaluated via three-point bending flexural tests. FRP laminates were produced with HealTechTM T300-TW200-42RW-1250, a commercially self-healing resin pre-impregnated Torayca T300 3K twill 2x2 fabric with aerial weight of 200g/m2. Fibers were oriented at ± 45°, or at 0-90° and the laminates were impacted at different energy levels. Flexural properties of undamaged, damaged and healed samples were compared, and the healing efficiency was calculated as the ratio of healed and undamaged ultimate flexural strength or modulus. Since matrix healing efficiency is the value to characterize, it was shown that ± 45° laminates could be tested without major fiber damage, and thus provide the best matrix healing efficiency results. Such method proved to be: i) representative of early-stage damage of composite FRPs often occurring in the form of delamination or matrix microcracking, ii) a fast and reliable characterization technique requiring the use of a limited amount of material.